Espiritismo e educação : Eurípedes Barsanulfo e o Colégio Allan Kardec / Sacramento-MG (1880-1918) - Silva, Jaqueline Peixoto Vieira da (2017)
The proposal of this work is the study of the relations among the memory of Eurípedes Barsanulfo and the College Allan Kardec, between 1880 and 1918. Barsanulfo is among the pioneers of spiritism in the Triângulo Mineiro region. He was a professor, alderman, founder of a college and a spiritist pharmacy, founder of the first urban spiritism center in Sacramento-MG and medium. He experienced an intense social life and was registered in the social frameworks memory with national and international recognition, mainly among spiritists. The Allan Kardec College, in the first period of operation (1907-1918), stood out as the first regular spiritist school in Brazil to offer free education and pioneering pedagogical methods in the early 20th century. This study was developed around the issues and problems of History and Memory. The individual and the college are nourished by the memory exercised. A memory that positions Barsanulfo as one of the canons of the spiritist religious social movement in Brazil, highlighted among the spirit mediums and remembered in the places of memory, is among the important characters for the spiritists. The problem developed in the study was towards the understanding of the social movement formation with the theoretical Kardequian base in the Triângulo Mineiro region. A movement initiated from individuals and spiritual families, in a mostly Catholic region that experienced ideological confrontations in the passage from the nineteenth century to the twentieth. In this study, it is argued that understanding the formation of Spiritist identity and representation is fundamental for the understanding of religious social movement that reaches the present days. Using theoretical frameworks for memory and educational history studies, the research methodology was based on the study and investigation of the first memorialist narratives on Barsanulfo and Allan Kardec College. The anthropological actions of observation and research in the places of memory that refer in Barsanulfo and to the Allan Kardec College in the city of Sacramento, Uberaba and Uberlândia were also important, with visits to spiritist houses, museums and spiritist meetings. The results show the formation of the spiritist religious social movement in the Triângulo Mineiro region, with a construction of representation and identity from the memory of Barsanulfo and the College Allan Kardec.